2021
DOI: 10.1155/2021/6688724
|View full text |Cite
|
Sign up to set email alerts
|

Shear Properties and Mechanism of Freeze‐Thaw Interface in Unsaturated Coarse‐Grained Soil from Qinghai‐Tibet Plateau

Abstract: Freeze-thaw interface in unsaturated coarse-grained soil (CGS) is a weak plane which can cause slope failures in cold regions. This study presents a series of large-scale direct shear tests on freeze-thaw interface in CGS through a temperature control system. The tested soil was taken from a high slope in the Qinghai-Tibet Plateau. It was remolded with three dry densities (1.9, 2.0, and 2.15 g/cm3) and three moisture contents (9.0%, 11.5%, and 14.0%). With testing results, direct shear curves mainly performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…In freeze-thaw-related studies, many experts and scholars have used cohesion and the internal friction angle as indicators of soil changes and investigated the freeze-thaw damage mechanism [23][24][25]. Jilin Qi et al [26,27] carried out direct shear tests on soils and found that changes in the dry density affected the cohesion, and the cohesion decreased when the dry density exceeded the critical density. Jiankun Liu et al [28] suggested that the cohesion and internal friction angle of fly ash decreased most in the first cycle and reached their minimum values after seven-nine cycles.…”
Section: Introductionmentioning
confidence: 99%
“…In freeze-thaw-related studies, many experts and scholars have used cohesion and the internal friction angle as indicators of soil changes and investigated the freeze-thaw damage mechanism [23][24][25]. Jilin Qi et al [26,27] carried out direct shear tests on soils and found that changes in the dry density affected the cohesion, and the cohesion decreased when the dry density exceeded the critical density. Jiankun Liu et al [28] suggested that the cohesion and internal friction angle of fly ash decreased most in the first cycle and reached their minimum values after seven-nine cycles.…”
Section: Introductionmentioning
confidence: 99%